Marketing analysis of fresh cayenne pepper fruit in Batukara District, Muna Regency, South East Sulawesi Province - Alimin, Alimin; Tandipayung, Serli (Sangia Research Media and Publishing, 2023)
Batukara District is the largest producer of cayenne pepper in Muna Regency, so it requires marketing channels that are profitable and fair. The aim of this research is to examine the distribution channels for fresh cayenne pepper from Batukara District and analyze the total margin and farmer share for each. Data was collected through face-to-face and by telephone. Data was analyzed descriptively qualitatively and quantitatively. The results of this research show: (1) The marketing channels for fresh cayenne pepper from Batukara District are: (a) Channel 1.a, starting with producers, collecting traders from Batukara District, wholesalers in Kendari City, retailers in Kendari City, ending to consumers in Kendari City; (b) Channel 1.b, starting with producers, collecting traders from Batukara District and Wakorumba District, wholesalers in Ambon City, retailers in Ambon City, ending with consumers in Ambon City; (c) Channel 2.a, starting with producers, collecting traders from Batukara District, retailers in village markets in Batukara District, ending with consumers in the Batukara District area; (d) Channel 2.b, starting with producers, collecting traders from Labuan, retailers at Labuan Market, ending with consumers in Wakorumba District; (e) Channel 3, starting with producers, retailers at Raha Central Market, ending with consumers in Raha City; (2) The total margin is an average of Rp. 33,000,-/kg; (3) Farmer share is an average of 60.93%.